Nilai Moral dalam Puisi-Puisi Karya Abidah El Khalieqy: Telaah Strukturalisme - Syipa An Nisa; Muharsyam Dwi Anantama (Jurusan Pendidikan Bahasa dan Seni Fakultas Keguruan dan Ilmu Pendidikan Universitas Lampung, 2025)
Literary works, including poetry, are not only created for aesthetic purposes, but also as a means of conveying ideas, views on life, and the author's response to the social reality around them. The function of poetry is inseparable from its role as a carrier of life values, including norms and morals that serve as guidelines in society. This study analyzes the moral values in Abidah El Khalieqy's poems through a qualitative approach with descriptive methods and content analysis techniques. The theory in this study refers to the structural theory of Nurgiantoro and Pradopo. Data in the form of physical and spiritual elements of poetry—words, phrases, and sentences—are identified to reveal three dimensions of moral values: (1) personal (gender equality, women's resilience, love of nature); (2) social (mutual love, cooperation); and (3) spiritual (obedience to worship, awareness of death). The research findings show that the structure of poetry is a medium for conveying complex moral messages, reflecting the poet's humanist-religious vision. Karya sastra, termasuk puisi, tidak hanya diciptakan untuk tujuan estetis semata, tetapi juga sebagai sarana penyampaian gagasan, pandangan hidup, dan respons pengarang terhadap realitas sosial di sekitarnya. Fungsi puisi tidak terlepas dari perannya sebagai pembawa nilai-nilai kehidupan, termasuk norma dan moral yang menjadi pedoman dalam bermasyarakat. Penelitian ini menganalisis nilai moral dalam puisi-puisi Abidah El Khalieqy melalui pendekatan kualitatif dengan metode deskriptif dan teknik analisis isi. Teori dalam penelitian ini mengacu pada teori struktural Nurgiyantoro dan Pradopo. Data berupa unsur fisik dan batin puisi— kata, frasa, dan kalimat—diidentifikasi untuk mengungkap tiga dimensi nilai moral: (1) personal (kesetaraan gender, ketangguhan perempuan, kecintaan pada alam); (2) sosial (saling menyayangi, kerja sama); dan (3) spiritual (ketaatan ibadah, kesadaran akan kematian). Temuan penelitian menunjukkan struktur puisi menjadi medium penyampaian pesan moral yang kompleks, merefleksikan visi humanis- religius penyair.